Methods to Determine Ductility of Structural Members: A Review - Jen Hua Ling; Yong Tat Lim; Euniza Jusli (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2023)
Ductility plays a crucial role in ensuring the safety of a structure, as its inadequacy can lead to sudden and brittle failure. Despite its significance, there is no explicit method for determining, leading to inconsistency and confusion in selecting appropriate techniques. Misjudging a structure’s ductile behaviour can have catastrophic consequences. Therefore, this study examined several preliminary studies and identified twenty-one methods for computing ductility indices. These indices were categorized into three types, namely conventional, displacement-based, and energy-based. The conventional ductility indices are commonly applied to steel-reinforced members, deformation-based ductility indices to FRP-reinforced members, and energy-based ductility indices to earthquake-resistant and static-load structures. Conventional ductility indices are specific to ductile reinforcements, while displacement-based and energy-based ductility indices apply to both ductile and non-ductile reinforcements. However, different calculation methods can lead to significant variations in the computed ductility, particularly for those involving the first crack, and load factor, thereby leading to different ductility requirements for ensuring structural safety. Additionally, not all methods are explicit, and it is crucial to avoid indiscriminately applying requirements from one method to another.